2021
DOI: 10.1111/jir.12858
|View full text |Cite
|
Sign up to set email alerts
|

Executive function as measured by the Behavior Rating Inventory of Executive Function‐2: children and adolescents with Williams syndrome

Abstract: Background Difficulties with executive functions (EF) are very common among individuals with Williams syndrome (WS). To characterise the pattern of relative strengths and weaknesses in EF for children and adolescents with WS, we considered the performance of a large sample on the parent version of the Behavior Rating Inventory of Executive Function-2 (BRIEF-2). Associations between distinct components of EF and adaptive behaviour, behaviour problems and intellectual ability were investigated. The concurrent ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Notably, recent case series on individuals with WSS (Ng, Harris, et al, 2023) also suggest some overlapping cognitive deficits seen among those with Williams syndrome (Bellugi et al, 2000), including marked deficits in visual–spatial processing and math skills in the context of relative sparing of verbal reasoning, receptive vocabulary, and sight‐word reading skills. Those with Williams syndrome show marked executive functioning deficits (Greiner de Magalhães et al, 2022), which was also observed among those with WSS, with more impairment reported in behavior and emotion regulation (Ng, Harris, et al, 2023). Accordingly, it is possible that the social patterns observed in our sample of WSS may reflect problems with executive control, poor response inhibition and dysfunction in the frontal lobe or frontostriatal circuits on modulating social behaviors—a proposed hypothesis for the hypersocial tendencies (poorly discriminatory approach behaviors) seen in those with Williams syndrome (Hanson et al, 2020; Mobbs et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…Notably, recent case series on individuals with WSS (Ng, Harris, et al, 2023) also suggest some overlapping cognitive deficits seen among those with Williams syndrome (Bellugi et al, 2000), including marked deficits in visual–spatial processing and math skills in the context of relative sparing of verbal reasoning, receptive vocabulary, and sight‐word reading skills. Those with Williams syndrome show marked executive functioning deficits (Greiner de Magalhães et al, 2022), which was also observed among those with WSS, with more impairment reported in behavior and emotion regulation (Ng, Harris, et al, 2023). Accordingly, it is possible that the social patterns observed in our sample of WSS may reflect problems with executive control, poor response inhibition and dysfunction in the frontal lobe or frontostriatal circuits on modulating social behaviors—a proposed hypothesis for the hypersocial tendencies (poorly discriminatory approach behaviors) seen in those with Williams syndrome (Hanson et al, 2020; Mobbs et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…Also, several papers in this special issue reach the conclusion that proxy‐report measures used to assess EF in the general population, such as the BRIEF and its different forms, might are sensitive tools for identifying difficulties and profiles at least for some specific ID aetiologies such as Down and Williams syndrome (Csumitta et al . 2022; Greiner de Magalhaes et al ., 2022; Onnivello et al . 2022).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Two other neurogenetic conditions were also examined in the present special issue, Williams syndrome and Prader-Willi syndrome, generating converging findings regarding the link between overall intellectual functioning and the EF component process of cognitive flexibility. Greiner de Magalhães et al (2022) report on BRIEF-2 (Gioia et al 2015) parent data for a large sample of 6to 17-year-old children and adolescents with Williams syndrome. They found that the cognitive regulation index posed the greatest area of challenge at the group level.…”
Section: Aetiology-specific Findingsmentioning
confidence: 99%